Implementasi Metode Goal Programming Untuk Optimasi Produksi Cokelat Pada UMKM - Pradjaningsih, Agustina; Andora, Ela; Santoso, Kiswara Agung (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2024)
Chocolate is a food made from cocoa beans, namely Theobroma Cacao. Cocoa beans harvested are then processed to prevent rotting, which can reduce their quality. Currently, many chocolate manufacturers produce various variants of chocolate products. Each production company tries to achieve maximum profits with minimal costs. Production optimization problems can be addressed using objective programming, which is a method used to develop mathematical models of optimization problems involving multiple objectives or constraints. In goal programming, each goal is expressed as a goal constraint. Objective programming methods involve determining decision variables, objective constraints, and objective functions. Optimization problems are solved using the objective programming method with the help of Lingo software. Optimization calculations using Lingo software show that the production of each chocolate product has reached optimality. Production after optimization reached Rp. 10,380,000 per month, whereas production costs were only Rp. 10,500,000 per month before optimization. The availability of raw materials needed after optimization reached 85 recipes per month, whereas it was 90 recipes per month before optimization. The profit obtained is also optimal, namely Rp. 4,267,000 in one month.